Conflictividad y usos sociales en la elite encomendera de Córdoba del Tucumán (Virreinato del Perú- 1573-1700 - Constanza González Navarro; Romina Grana (Nuevo mundo - Mundos Nuevos, 2013)
This work is framed in the study of the social practices and uses employed by the elite “encomendera” of Córdoba del Tucumán in the resolution of inter-ethnic and intra-ethnic conflicts at the end of the 16th century. These practices -were they institutionalized or not- were not ignored by the judicial local authorities; on the contrary, they were frequently accepted by them. We attempt to recognize that in the colonial society the double action of the official justice and the social practices and uses operated and were carried out by the subjects. These subjects served the purpose of maintaining and strengthening the authority of the master inside the “encomienda, establishing social hierarchies, defending and preserving right, or just limiting the frames of tolerance of the colonial society vis-á-vis specific behaviours.